The Counsellor and His Asexual Client - McConnell, Lawrence G. (Canadian Journal of Counselling and Psychotherapy, 2012)
In terms of human sexuality, counsellors are trained to function as if living in a Victorian society. This is achieved by simply pretending that sex does not exist. The counsellor has a role to perform in assisting his clients to come to grips with their own sexuality. The counsellor's competence in this area is questioned. Competence involves training the counsellor in the area of human sexuality.